2020
DOI: 10.1002/2211-5463.12780
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: CDKL5 promotes proliferation, migration, and chemotherapeutic drug resistance of glioma cells via activation of the PI3K/AKT signaling pathway

Abstract: Gliomas, the most prevalent cancer in the central nervous system, are characterized by high morbidity and mortality, emphasizing the need to understand their etiology. Here, we report that cyclin‐dependent kinase‐like 5 (CDKL5) is highly expressed in gliomas, and CDKL5 overexpression promotes invasion, proliferation, migration and drug (β‐lapachone) resistance of glioma cells. In vitro, CDKL5 overexpression enhanced invasion, growth and migration of glioma cells, and stimulated the phosphoinositide 3‐kinase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This information suggests that CDKL2 activation by HMI-1a3 could mediate the observed decrease in viability in colorectal cancer cells. The other three most activated kinases, intestinal cell kinase (ICK) (Whitworth et al, 2012), alpha-protein kinase (AlphaK1) (Chen et al, 2019) and cyclin-dependent kinase-like 5 (CDKL5) (Jiang et al, 2019), are associated with tumour growth and aggressiveness. Being among the most activated kinases, according to the upstream kinase interpretation, cyclic AMP-dependent protein kinase A (PKA) and cyclic GMP-dependent protein kinase G (PKG) also demonstrated high specificity score or consistency in activity on both time points (Tables 1 and 2, Supplementary Figures S3 and S4).…”
Section: Early Effects Of Hmi-1a3 On Kinase Activity Of Colo205 Cellsmentioning
confidence: 99%
“…This information suggests that CDKL2 activation by HMI-1a3 could mediate the observed decrease in viability in colorectal cancer cells. The other three most activated kinases, intestinal cell kinase (ICK) (Whitworth et al, 2012), alpha-protein kinase (AlphaK1) (Chen et al, 2019) and cyclin-dependent kinase-like 5 (CDKL5) (Jiang et al, 2019), are associated with tumour growth and aggressiveness. Being among the most activated kinases, according to the upstream kinase interpretation, cyclic AMP-dependent protein kinase A (PKA) and cyclic GMP-dependent protein kinase G (PKG) also demonstrated high specificity score or consistency in activity on both time points (Tables 1 and 2, Supplementary Figures S3 and S4).…”
Section: Early Effects Of Hmi-1a3 On Kinase Activity Of Colo205 Cellsmentioning
confidence: 99%
“…The PI3K–AKT pathway has been well-studied as a molecular escape route for cells to avoid death ( 37 ). In the context of resistance to chemotherapeutic drugs, it is well-known that activation of the PI3K–AKT pathway not only occurs but also has an important role in multidrug resistance ( 38 ). According to Yang et al, AKT promotes resistance to cisplatin in ovarian cancer cell lines by modulating P53 on the caspase-dependent mitochondrial death pathway ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CDKL5 localizes at multiple subcellular structures [26,27], and involved in cell division [26]. The association between CDKL5 and drug resistance was identi ed [28,29]. In vitro experiments suggested that knockdown of CDKL5 and LINC00680 decreased the expression of MDR1, MRP5 and LRP1 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The role of MDR1 and MRP7 in docetaxel resistance were demonstrated in different types of cancer [34][35][36][37]. As shown by Jiang et al [29], CDKL5 promotes chemotherapeutic drug resistance of glioma may through PI3K/AKT pathway. Our study hinted that the expression of CDKL5 and LINC00680 together with chemo-resistance genes MDR1, MRP5 and LRP1 play an important role in docetaxel resistance of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation